Postcranial elements of "Maledictosuchus riclaensis" (Thalattosuchia) from the Middle Jurassic of Spain - Parrilla-Bel, J.; Canudo, J.I. (Journal of Iberian Geology, 2015)
Maledictosuchus riclaensis is a metriorhynchid crocodylomorph from the Callovian (Middle Jurassic) of Ricla (Spain). It is the most basal member of the Rhacheosaurini Tribe; it has recently been described and defined by its cranial elements (an almost complete skull and part of the lower jaw), but there were no data on the postcranial elements. Associated with the skull three vertebrae were collected. These vertebrae were preserved in black calcite nodules, and they have recently been prepared. The postcranial elements of the metriorhynchids are poorly documented, and usually badly preserved or included in the matrix. Herein we describe the three vertebrae (part of the holotype) of M. riclaensis. These comprise one cervical, one dorsal and one caudal vertebra, which, like the skull, are well preserved and lack postmortem distortion or deformation.